The effectiveness of problem-based learning on students creative thinking: a meta-analysis study - Mustakim, Siti Salina; Li, Lu; Muhamad, Mohd Mokhtar (South East Asian Association for Institutional Research, 2024)
PBL can significantly improve students’ creative thinking than the conventional method. The subgroup analyses also revealed that the improvement of students’ creative thinking in PBL was not affected by the experimental measurements, teaching methods, or the size of the sample but varied significantly across different education stages and subjects.